2018
DOI: 10.1111/inm.12470
|View full text |Cite
|
Sign up to set email alerts
|

Colocating an accredited practising dietitian to an adult community mental health service: An exploratory study

Abstract: For people with severe mental illness, accredited practising dietitians may assist with a nutrition care plan that considers the medical, psychiatric, psychological, social, spiritual, and pharmacological aspects of their care. However, consumers' access to care has been limited by difficulties attending appointments and suboptimal interface between nutritional and mental health services. Therefore, the objectives of this exploratory study were to describe access to, and key stakeholder perspectives of, the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…This should be a priority given the long‐term impacts on physical health 47 and education outcomes 48 for young people experiencing food insecurity over their lifespan. Most relevant for this study are the long‐term impacts on mental health, where food insecurity in childhood has been shown to be associated with a higher risk of mental health issues in adolescents and young adults 49 . Regardless of food security status, this study showed that dietary intake of fruits, vegetables and breakfast was poor, and respondents regularly consumed takeaway foods and sugar‐sweetened beverages.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This should be a priority given the long‐term impacts on physical health 47 and education outcomes 48 for young people experiencing food insecurity over their lifespan. Most relevant for this study are the long‐term impacts on mental health, where food insecurity in childhood has been shown to be associated with a higher risk of mental health issues in adolescents and young adults 49 . Regardless of food security status, this study showed that dietary intake of fruits, vegetables and breakfast was poor, and respondents regularly consumed takeaway foods and sugar‐sweetened beverages.…”
Section: Discussionmentioning
confidence: 77%
“…Most relevant for this study are the long-term impacts on mental health, where food insecurity in childhood has been shown to be associated with a higher risk of mental health issues in adolescents and young adults. 49 Regardless of food security status, this study showed that dietary intake of fruits, vegetables and breakfast was poor, and respondents regularly consumed takeaway foods and sugar-sweetened beverages. The results of this study could be utilised by managers and funders of youth mental health services to inform changes in service delivery that support improving diet.…”
Section: Discussionmentioning
confidence: 81%
“…Consumers found the NPCs’ practices to be positive and helpful, and reported associated physical and mental health improvements. When consumers feel supported by clinicians they can engage in healthy practices (Bartlem et al ) and this has resulted in beneficial changes in modifiable risk factors of cardiovascular and cardiometabolic diseases such as nicotine dependence (Tsoi et al ), sedentary lifestyles (Furness et al ), and poor nutritional status (Furness et al ). The consumer experiences, and cardiovascular and metabolic monitoring outcomes in the current study suggest that NPC advanced practice roles are a vital resource that can provide quality physical health care and directly serve to improve the substantial morbidity and mortality of consumers.…”
Section: Discussionmentioning
confidence: 99%
“…The poor physical health of people with severe mental illness (consumers) is a global concern (World Health Organization ). Despite increasing evidence of consumers’ poor physical health and efforts to prevent morbidity (Baxter et al ; Furness et al ; Hughes et al ), their mortality age is disproportionately younger compared with the general population (Correll et al ; Nemani et al ). Recognized co‐occurring physical health conditions for consumers include poor cardiovascular (Brobakken et al ), respiratory (Jørgensen et al ), and cardiometabolic (Yoca et al ) health.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, consumers are reported to have poor nutritional intake (Furness et al . 2018a) and high occurrence of hypertension (Ayerbe et al . 2018) and hyperglycaemia (Kang & Lee 2015).…”
Section: Introductionmentioning
confidence: 99%